Исследование механических напряжений в приводном валу вакуумного выключателя средних напряжений - Байда, Е.И.; Клименко, Б.В. (Електротехніка і електромеханіка, 2017)
В статье исследуются процессы, которые определяют механические напряжения в приводном вале вакуумного выключателя в статическом и динамическом режимах работы. Показано, что механическая деформация вала вызывает уменьшение провала контактов на величину до 30% и сил контактного нажатия на (10-11)%, эти значения не
критичны и мало влияют на работу выключателя. Получены значения сил, действующих на опоры вала. Показано,
что динамические усилия в опорах на (19-38)% больше статических. Полученные значения усилий позволяют выбрать материал вала и подшипники. У статті досліджуються процеси, що визначають механічні напруги в приводному валу вакуумного відмикача в статичному та динамічному режимах роботи. Показано, що механічна деформація вала обумовлює зменшення провалу контактів до 30% і сил контактного натискання на (10-11)%, однак ці значення не є критичними та мало впливають на роботу вимикача. Отримано значення сил, що діють на опори вала. Показано, що динамічні сили в опорах на (19-38)%
більше, ніж статичні. Отримані значення зусиль дозволяють вибрати матеріал вала та підшипники. Introduction. In the last 10-15 years a dominant position in the
market of medium voltage circuit breakers, vacuum circuit breakers
have taken in which as an actuator mono- or bistable actuators with
permanent magnets are used. Such circuit breakers are characterized by simplicity of design, high reliability, require preventive
maintenance for many years. Development, research and improvement of vacuum circuit breakers are carried out at the Department
for Electrical Apparatus, National Technical University «Kharkiv
Polytechnic Institute». While working on the circuit breakers, developers have to deal with two related objectives – electrical and
mechanical. This paper considers the solution of one of these problems – calculation of mechanical forces in the drive shaft of the
vacuum circuit breaker in static and dynamic modes. This work was
preceded by the failure of the results of measurements of the prototype circuit breakers’ contacts. Measurements have shown that
these values do not match the expected values (there were less than
the value of 0.8 to 1 mm). The assumption about the reasons for this
discrepancy needed to be detailed checked. The results of the work
done are presented in this paper. Purpose. Investigation of static
and dynamic mechanical stresses and strains in the drive shaft of
the vacuum circuit breaker mechanism to determine its characteristics and material selection. Methods. The investigation of mechanical processes is performed by the finite element method in the
COMSOL software package. Results. We obtain the static and dynamic characteristics of the circuit breaker drive shaft: deformations, reaction forces, stresses. These characteristics made it possible to determine the actual course of the contacts, select shaft material and calculate the forces acting on the bearings. Conclusions. It
is shown that the contact velocity and contact pressure are different
from the theoretical value due to the deformation of the shaft. The
forces acting on the thrust bearings dynamically are by 16-39%
higher than the static ones. It is assumed that further refinement of
the mathematical model takes into account the traction insulators
and housing, as well as dynamics of the circuit.